View Single Post
Old 2018-03-06, 18:35   #20
JM Montolio A
 
Feb 2018

1408 Posts
Default

I put some trace on the code.

n 3
n 3 + e 1 = (2^g 2)(e' 1)
n 3 M 2 Dbit 1 D 1

n 5
n 5 + e 1 = (2^g 1)(e' 3)
n 5 + e 3 = (2^g 3)(e' 1)
n 5 M 4 Dbit 2 D 3

n 7
n 7 + e 1 = (2^g 3)(e' 1)
n 7 M 3 Dbit 1 D 1

n 9
n 9 + e 1 = (2^g 1)(e' 5)
n 9 + e 5 = (2^g 1)(e' 7)
n 9 + e 7 = (2^g 4)(e' 1)
n 9 M 6 Dbit 3 D 7

n 11
n 11 + e 1 = (2^g 2)(e' 3)
n 11 + e 3 = (2^g 1)(e' 7)
n 11 + e 7 = (2^g 1)(e' 9)
n 11 + e 9 = (2^g 2)(e' 5)
n 11 + e 5 = (2^g 4)(e' 1)
n 11 M 10 Dbit 5 D 93

n 13
n 13 + e 1 = (2^g 1)(e' 7)
n 13 + e 7 = (2^g 2)(e' 5)
n 13 + e 5 = (2^g 1)(e' 9)
n 13 + e 9 = (2^g 1)(e' 11)
n 13 + e 11 = (2^g 3)(e' 3)
n 13 + e 3 = (2^g 4)(e' 1)
n 13 M 12 Dbit 6 D 315

n 15
n 15 + e 1 = (2^g 4)(e' 1)
n 15 M 4 Dbit 1 D 1

n 17
n 17 + e 1 = (2^g 1)(e' 9)
n 17 + e 9 = (2^g 1)(e' 13)
n 17 + e 13 = (2^g 1)(e' 15)
n 17 + e 15 = (2^g 5)(e' 1)
n 17 M 8 Dbit 4 D 15

n 19
n 19 + e 1 = (2^g 2)(e' 5)
n 19 + e 5 = (2^g 3)(e' 3)
n 19 + e 3 = (2^g 1)(e' 11)
n 19 + e 11 = (2^g 1)(e' 15)
n 19 + e 15 = (2^g 1)(e' 17)
n 19 + e 17 = (2^g 2)(e' 9)
n 19 + e 9 = (2^g 2)(e' 7)
n 19 + e 7 = (2^g 1)(e' 13)
n 19 + e 13 = (2^g 5)(e' 1)
n 19 M 18 Dbit 9 D 13797

n 21
n 21 + e 1 = (2^g 1)(e' 11)
n 21 + e 11 = (2^g 5)(e' 1)
n 21 M 6 Dbit 2 D 3

n 23
n 23 + e 1 = (2^g 3)(e' 3)
n 23 + e 3 = (2^g 1)(e' 13)
n 23 + e 13 = (2^g 2)(e' 9)
n 23 + e 9 = (2^g 5)(e' 1)
n 23 M 11 Dbit 4 D 89

n 25
n 25 + e 1 = (2^g 1)(e' 13)
n 25 + e 13 = (2^g 1)(e' 19)
n 25 + e 19 = (2^g 2)(e' 11)
n 25 + e 11 = (2^g 2)(e' 9)
n 25 + e 9 = (2^g 1)(e' 17)
n 25 + e 17 = (2^g 1)(e' 21)
n 25 + e 21 = (2^g 1)(e' 23)
n 25 + e 23 = (2^g 4)(e' 3)
n 25 + e 3 = (2^g 2)(e' 7)
n 25 + e 7 = (2^g 5)(e' 1)
n 25 M 20 Dbit 10 D 41943

n 27
n 27 + e 1 = (2^g 2)(e' 7)
n 27 + e 7 = (2^g 1)(e' 17)
n 27 + e 17 = (2^g 2)(e' 11)
n 27 + e 11 = (2^g 1)(e' 19)
n 27 + e 19 = (2^g 1)(e' 23)
n 27 + e 23 = (2^g 1)(e' 25)
n 27 + e 25 = (2^g 2)(e' 13)
n 27 + e 13 = (2^g 3)(e' 5)
n 27 + e 5 = (2^g 5)(e' 1)
n 27 M 18 Dbit 9 D 9709

n 29
n 29 + e 1 = (2^g 1)(e' 15)
n 29 + e 15 = (2^g 2)(e' 11)
n 29 + e 11 = (2^g 3)(e' 5)
n 29 + e 5 = (2^g 1)(e' 17)
n 29 + e 17 = (2^g 1)(e' 23)
n 29 + e 23 = (2^g 2)(e' 13)
n 29 + e 13 = (2^g 1)(e' 21)
n 29 + e 21 = (2^g 1)(e' 25)
n 29 + e 25 = (2^g 1)(e' 27)
n 29 + e 27 = (2^g 3)(e' 7)
n 29 + e 7 = (2^g 2)(e' 9)
n 29 + e 9 = (2^g 1)(e' 19)
n 29 + e 19 = (2^g 4)(e' 3)
n 29 + e 3 = (2^g 5)(e' 1)
n 29 M 28 Dbit 14 D 9256395

n 31
n 31 + e 1 = (2^g 5)(e' 1)
n 31 M 5 Dbit 1 D 1
JM Montolio A is offline   Reply With Quote